SENIOR HIGH SCHOOL STUDENTS’ PERCEPTIONS OF USING SOCIAL MEDIA IN LEARNING ENGLISH IN POST COVID-19 PANDEMIC - Rahmawati, Fitria; Belinda, Fathya (University of Kuningan, 2024)
Despite the pandemic, many schools persist in giving priority to the exploitation of technology, especially social media. Social media provides numerous advantages for students, functioning as channels for communication, instruments for participation, and platforms for collaboration. This study investigates the use of social media in English learning by public senior high school students in Cirebon in the post covid-19 pandemic. The objective of this study is to discover the perspectives of senior high school students regarding the social media platforms they utilize for English language learning. Additionally, it seeks to determine the activities undertaken by students on social media for English language learning in the post Covid-19 pandemic. This study employed a descriptive qualitative methodology. The participants consisted of six students from a public senior high school in Cirebon. The researcher used interviews as the data collection. The results of the study revealed TikTok, YouTube, Instagram, Twitter or X, and WhatsApp as social media platforms that are utilized by senior high school students for English language learning. Furthermore, the English learning activities undertaken by senior high school students using social media include watching videos on social media, taking notes, commenting on social media’s live broadcasts, practicing English skills, interacting with others, and sharing learning media and materials. By integrating social media into English language instruction, this study offers educators valuable insights for developing engaging learning activities.Keywords: Post-pandemic; EFL learning; Social media; Social media platform; Learning activities